Temporal Assemblage and Distribution of Ephemeroptera in Lata Janggut, Jeli, Kelantan. Issue 1 (August 2020) - Mat Nazari, Nurul Natasha Izzati; Rak, Aweng Eh; Syed Omar, Sharifah Aisyah; Hajisamae, Sukree; Ahmad, Azlan; Ibrahim, Mohamad Zamzani
Abstract: Lata Janggut is one of the popular recreational rivers with waterfall in Jeli, Kelantan. The lotic river characteristic at Lata Janggut create a suitable habitat for aquatic insect especially Ephemeroptera. Recreational activities may disturb the river ecosystem especially aquatic insects, Ephermeroptera in particular. Therefore, this study targets to determine the temporal assemblage and distribution of Ephemroptera at Lata Janggut, Jeli from March till August 2019. Ephemeroptera collection was conducted monthly from March to August 2019 using Surber net for three replicates at three stations. In total, 1260 individuals with five (5) families (Ephemerellidae, Baetidae, Heptageniidae, Neophemeridae, and Leptobiilidae) and nine (9) genera were collected and recorded. The most abundant Ephemeroptera found is Baetidae and Emphemerellidae. However, the result shows the different composition for monthly abundance for those families. Meanwhile, the distribution of those families at all station also shows a different composition. This indicates there are microhabitat exists between the stations and the physical characteristic of the river has change monthly.